Answer:
The answer to your question is
[tex]\frac{(y - k)^{2}}{9} - \frac{(x - h)^{2} }{16} = 1[/tex]
Step-by-step explanation:
See the picture below
- From the picture we conclude that it is a vertical hyperbola
Center = (3, 2)
c = 5
a = 3 b² = c² - a² b² = 5² - 3² b² = 25 - 9 b² = 16
b = 4
- Equation
[tex]\frac{(y - k)^{2}}{a^{2} } - \frac{(x - h)^{2} }{b^{2}} = 1[/tex]
- Substitution
[tex]\frac{(y - 2)^{2}}{3^{2} } - \frac{(x - 3)^{2}}{4^{2}} = 1[/tex]
- Result
[tex]\frac{(y - k)^{2}}{9} - \frac{(x - h)^{2} }{16} = 1[/tex]